Alvimopan Provides Additional Improvement in Outcomes and Cost Savings in Enhanced Recovery Colorectal Surgery. Issue 1 (July 2016) - Adam, Mohamed Abdelgadir; Lee, Lacey M.; Kim, Jina; Shenoi, Mithun; Mallipeddi, Mohan; Aziz, Hamza; Stinnett, Sandra; Sun, Zhifei; Mantyh, Christopher R.; Thacker, Julie K. M.
Abstract : Objective: To examine the impact of alvimopan on outcomes and costs in a rigorous enhanced recovery colorectal surgery protocol. Background: Postoperative ileus remains a major source of morbidity and costs in colorectal surgery. Alvimopan has been shown to reduce incidence of postoperative ileus in enhanced recovery colorectal surgery; however, data are equivocal regarding its benefit in reducing length of stay and costs. Methods: Patients undergoing major elective enhanced recovery colorectal surgery were identified from a prospectively-collected database (2010–2013). Multivariable analyses were employed to compare outcomes and hospital costs among patients who had alvimopan versus no alvimopan by adjusting for demographic, clinical, and treatment characteristics. Results: A total of 660 patients were included; 197 patients received alvimopan and 463 patients had no alvimopan. In unadjusted analysis, the alvimopan group had a faster return of bowel function, shorter length of stay, and lower rates of ileus, Foley re-insertion, and urinary tract infection (all P  < 0.01). After adjustment, alvimopan was associated with a faster return of bowel function by 0.6 day ( P  = 0.0006), and lower incidence of postoperative ileus (odds ratio 0.23, P  = 0.0002). With adjustment, alvimopan was associated with a shorter length of stay by 1.6 days ( P  = 0.002), and a hospital cost savings of $1492 per patient ( P  = 0.01). Conclusions: Alvimopan administration as an element of enhanced recovery colorectal surgery is associated with faster return of bowel function, lower incidence of postoperative ileus, shorter hospitalization, and a significant cost savings. These results suggest that alvimopan is cost-effective in the setting of enhanced recovery colorectal surgery protocols, and should therefore be considered in these programs.